ABSENCE OF THE CELIAC TRUNK: A CASE REPORT - Pavlović Stojanovic, Jasmina; Perović, Aleksandra; Stojanovic, Minja; Kosanovic, Tijana; Radanovic, Djordje; Lazic, Ljiljana; Antonijevic Djordjevic, Dragana; Bijelica, Magdalena (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: The celiac trunk is an arterial trunk that has been the subject of numerous anatomical and radiological studies. From its origin, at the front of the abdominal aorta, the trunk extends for 1.5 – 2 cm and then divides into three branches: the left gastric artery, the common hepatic artery and the splenic artery. This type of trifurcation was first described by Haller, in 1756, and is considered the most common anatomical pattern. Anatomical variations of the celiac trunk are numerous, both in terms of branching and dimensions. The complete absence of the celiac trunk is a rare anatomical variation, wherein all three branches arise directly and independently from the abdominal aorta. Case report: A 63-year-old oncology patient was referred to the radiology department for an MR examination of the abdomen, in order to differentially diagnose changes in the adrenal glands. During the examination, complete absence of the celiac trunk was observed. The left gastric artery, splenic artery, and common hepatic artery arose directly and independently from the abdominal aorta. Conclusion: A variation of this type is mostly asymptomatic and has no negative effect on the blood supply of visceral organs. In literature, the prevalence of this vascular pattern ranges from 0.1% to 4%. Knowledge of vascular variations in the abdomen is very important during surgical, diagnostic and endovascular procedures.